Importance of short-term continuing care plan adherence on long-term outcomes among patients discharged from residential substance use treatment. (2nd November 2017) - Proctor, Steven L.; Wainwright, Jaclyn L.; Herschman, Philip L.
ABSTRACT: Background : Patients adherent to their recommended treatment regimen demonstrate favorable outcomes. However, it is unclear whether there are specific short-term continuing care performance variables indicative of better long-term prognosis. Objective : This study determined the impact of attendance at an outpatient appointment within 7 days post-discharge from residential treatment on 12-month outcomes. Method : Data were abstracted from electronic medical records for 275 patients (58.9% male) discharged from a single residential treatment program. All discharge plans included a 7-day outpatient appointment with a provider in their home community. Patients were dichotomized based on their attendance at the initial appointment to yield a re-engagement variable. Twelve-month outcomes included past 30-day and continuous abstinence rates, quality of life, and long-term adherence to continuing care plans. Results : Patients attending their initial outpatient appointment within 7 days of discharge evidenced better long-term outcomes relative to patients who did not with respect to continuous abstinence (75.4% vs. 37.3%), past-30-day abstinence (92.0% vs. 70.6%), quality of life (94.2% vs. 78.4%), and adherence (66.4% vs. 9.8%). Re-engagement remained a significant predictor of continuous abstinence and quality of life at 12 months after controlling for 12-month adherence and relevant demographic characteristics. Conclusion : Treatment providers are encouraged to emphasize the relative importance of attending initial post-discharge appointments in achieving successful long-term outcomes. Allocation of resources to enhance engagement during residential treatment may be justified in that there may be value in actively encouraging patients to participate in continuing care activities, particularly shortly following discharge.